2015
DOI: 10.1124/jpet.115.224659
|View full text |Cite
|
Sign up to set email alerts
|

Different 2-Aminothiazole Therapeutics Produce Distinct Patterns of Scrapie Prion Neuropathology in Mouse Brains

Abstract: Because no drug exists that halts or even slows any neurodegenerative disease, developing effective therapeutics for any prion disorder is urgent. We recently reported two compounds (IND24 and IND81) with the 2-aminothiazole (2-AMT) chemical scaffold that almost doubled the incubation times in scrapie prion-infected, wild-type (wt) FVB mice when given in a liquid diet. Remarkably, oral prophylactic treatment with IND24 beginning 14 days prior to intracerebral prion inoculation extended survival from ∼120 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 40 publications
0
63
0
Order By: Relevance
“…Studies with IND24 showed unexpected effects on efficacy when dosing was started later and when the mouse models and prion strains were varied (Berry et al, 2013;Berry et al, 2015;Giles et al, 2015). In addition, prophylactic dosing with IND24 was more effective at extending survival than continuous dosing starting after inoculation .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies with IND24 showed unexpected effects on efficacy when dosing was started later and when the mouse models and prion strains were varied (Berry et al, 2013;Berry et al, 2015;Giles et al, 2015). In addition, prophylactic dosing with IND24 was more effective at extending survival than continuous dosing starting after inoculation .…”
Section: Discussionmentioning
confidence: 99%
“…Such compounds were extended to long-term efficacy studies. We have now reported efficacy for 10 compounds in RML-infected mice: six 2-AMTs (Berry et al, 2013;Giles et al, 2015) and the four aryl amides described here. Remarkably, all 10 extend the survival of prion-infected mice, many by 2-fold or more.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations